Cluster Preface: Resurgence of Synthetic Aromatic Chemistry - Snieckus, Victor; Knochel, Paul (Synlett, 2015)
Victor Snieckus was born in Lithuania and fled with his parents to Germany during World War II. He obtained the B.Sc. at the University of Alberta, graduate degrees at University of California, Berkeley (D. S. Noyce) and University of Oregon (V. Boekelheide), and carried out postdoctoral studies at NRC Ottawa (O. E. Edwards). He taught at the University of Waterloo until 1998, then moved to Queen’s University, Kingston as the inaugural Bader Chair of Organic Chemistry. He continues fundamental research as Bader Chair Emeritus as well as Director of Snieckus Innovations, an institute for the synthesis of small molecules for the pharmaceutical and agrochemical industries. He is a recipient of the ACS Cope Scholar Award, Arfvedson-Schlenk Preis of the GDCh, CSC Bernard Belleau and Alfred Bader Awards, is a Lithuanian Academy of Sciences Laureate, and is a Royal Society of Canada Fellow. He infrequently plays hockey and wishes he had not given up the clarinet. Paul Knochel was born 1955 in Strasbourg (France). He did his undergraduate studies at the University of Strasbourg (France) and his Ph.D at the ETH Zürich with Prof. D. Seebach. He spent four years at the CNRS at the University Pierre and Marie Curie in Paris with Prof. J.-F. Normant and one year of post-doctoral studies at Princeton University in the laboratory of Prof. M. F. Semmelhack. In 1987, he accepted a position as Assistant Professor at the University of Michigan at Ann Arbor, Michigan. In 1991, he became Full Professor at this University and in 1992, he moved to Philipps-University at Marburg (Germany) as C4-Professor in Organic Chemistry. In 1999, he moved to the Chemistry Department of Ludwig-Maximilians-University in Munich (Germany). His research interests include the development of novel organometallic reagents and methods for use in organic synthesis, asymmetric catalysis and natural product synthesis. Prof. Knochel received many distinguished prices as e.g. the Berthelot Medal of the Academie des Sciences (Paris), the IUPAC Thieme Prize, the Otto-Bayer-Prize, the Leibniz-Prize (1.500.000 Euro), the Arthur C. Cope Scholar Award, Karl-Ziegler-Prize, the Nagoya Gold Medal, the H. C. Brown Award and Paul Karrer gold medal. He is member of the Académie des Sciences (France), the Bavarian Academy of Science, the German Academy of Sciences Leopodina, and the Center for Advanced Studies.